Nellie Ernestine Horne: vida professoral de uma educadora canadense na Paraíba(1934-1968) - Urban, Adriana Oliveira (2020)
The dissertation entitled Nellie Ernestine Horne: the professorial life of a Canadian educator based in Paraíba (1934-1983), aims to narrate the professorial trajectory of Horne since leaving Toronto in 1934, her hometown, and arriving in Patos-Paraíba, in 1935. This work will show her educational contributions as a teacher and later on director of Bethel Bible Institute, which she co-founded. This work will demonstrate that teaching was understood by Nellie Ernestine Horne as her life mission: she believed she was vocacionaly called to teaching. Through it she also put into practice her religious beliefs of Protestant nature when teaching her students and other interns at the school she founded with a professional colleague in Patos, Paraíba, in 1935. The historical outline shows the arrival of Ernestine Horne in Brazil, in 1934, until 1968, the last year in which she served as director of the Bethel Bible Institute. The pillars that supported her convictions were religion and education. Both are constantly perceptible throughout Horne’s life. This research writing demonstrates how these pillars uphold her way of living and the methods of teaching in her legacy as a teacher in the formation of missionary educators, as well as in the spreading of the Protestant faith by founding and helping to plant evangelical churches. This study is a theoretical and methodological approach of the New Cultural History, using autobiographical documents such as letters, personal diaries, notebooks, records and albums. These documents disclose remarkable moments of the daily life of the Canadian teacher, revealing information that helps complement in the narrative of her calling and teaching trajectory. This trajectory took place essentially among women and many of them experienced financial ascension through their teacher training. In addition it also made possible the opening of social spaces, but without the use of feminist approaches. In summary Horne’s educator journey was fulfilled, as she writes, by teaching as a vocation in her life. Former students of the Canadian teacher also testified and experienced her teaching gifts.